Isotopic and trace element data of Tissint indicate a homogeneous strewn field, mobilization of Sr, REE, and Pb during shock metamorphism, and limits on the incorporation of martian surficial materials in impact melt glass. (15th June 2022) - Suarez, S.E.; Lapen, T.J.; Righter, M.; Beard, B.L.; Irving, A.J.
Abstract: The Tissint strewn field has produced over 16 kg of material that has minimal terrestrial weathering and/or contamination. Tissint, along with 16 other incompatible trace element (ITE)-depleted shergottite specimens with igneous crystallization ages spanning 327–2403 Ma, were ejected together from Mars 1.1 m.y. ago. Despite the geochemical similarities of fragments from the Tissint strewn field, there are reported discrepancies in age determinations from different fragments that raise the possibility that the strewn field may be heterogenous. There are also questions about whether the shock ejection event incorporated martian soil components into impact glass, and the sources of radiogenic Sr and Pb that have been measured from leachate fractions in previous studies. An impact melt-rich fragment of Tissint was analyzed by LA-ICPMS for rare-earth element (REE) and highly siderophile element (HSE) concentrations and Pb isotopic compositions. Leachate and residues from 8 specimens representing separate individual fragments collected from the strewn field were analyzed for Rb-Sr. Unleached fractions of the 8 specimens were also analyzed for Sm-Nd and Lu-Hf. The measured REE and HSE concentrations of impact melt glass and associated sulfide measured by LA-ICPMS are consistent with bulk rock compositions of Tissint and show no evidence for incorporation of more ITE-enriched martian surface components. Measured Pb isotopic compositions confirm that the impact melt glass and associated sulfide contain no evidence for incorporation of more radiogenic materials than the Pb compositions inherited from the primary magma. In situ Pb isotopic data from sulfide likely represents the most robust method for constraining initial Pb isotopic compositions of shergottites whereas approaches that rely on leaching and digestion may not remove all mineral and/or crack surface contaminants. Rubidium-strontium analyses of the 8 Tissint specimens indicate that labile components hosting HCl-soluble Rb and Sr are not in isotopic equilibrium with the igneous assemblage and that the washed residues are in isotopic equilibrium with the igneous assemblage. The Sr isotopic compositions of the leachate are within the range of 'more ITE-enriched' depleted shergottites, perhaps indicating sources from the igneous pile on Mars. The radiogenic Sr component could represent crack and mineral surface coatings of volatilized materials derived from nearby depleted shergottite rock units during the impact ejection process but are not radiogenic enough to represent ITE-enriched crust or mantle components. The Lu-Hf isotopic data from the specimens indicate no evidence of contamination or element mobility, whereas the Rb-Sr and Sm-Nd isotopic systems show evidence for element mobility and potential mixing with an isotopic component not in equilibrium with the igneous phases. The calculated ages using data compiled from Brennecka et al. (2014), and Grosshans (2013) for Lu-Hf, Rb-Sr, and Sm-Nd are 571 ± 84 Ma, 590 ± 49 Ma and 559 ± 39 Ma, respectively. These data indicate that the specimens analyzed here are cogenetic and the Tissint strewn field appears to be homogeneous.